A supported metal porphyrin complex, preparation method and application thereof
By using the load -type metal pyrine mathematical as a catalyst, the existing catalysts have insufficient activity and metal residues in the co -reaction of carbon dioxide and epoxy carbon dioxide and metal residues, and have achieved efficient catalytic and high recycling, which improves the quality and quality of polymer products and the quality of polymer Environmental protection.
Patent Information
- Application Number
- CN202210508275.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-11
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-05-11
AI Technical Summary
The existing catalysts have problems of insufficient activity, poor polymer quality, metal residues and difficult-to-control by-products in the copolymerization reaction of carbon dioxide and epoxides.
The load -type metal pyrine complex is used as a catalyst. The mathematical is composed of a carrier, link group, and metal pyrine -linoline complex. It is loaded on the carrier through chemical links to achieve non -equalization and easy separation.
The high activity, high selective and high recycling utilization rate of catalysts is realized, the metal residues in the polymer are reduced, and the quality and environmental protection of the polymerization products are improved.
Smart Images

Figure CN114989207B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a supported metal porphyrin complex, a preparation method and an application thereof. Background Art
[0002] Carbon dioxide is an ideal C1 resource with abundant reserves. Its recycling is expected to meet the development of industrialization and improve environmental benefits. Alternating copolymerization of carbon dioxide and epoxide can produce fully degradable polycarbonate, which provides a good substitute for increasingly scarce non-renewable resources such as petroleum. Through the path of carbon cycle, we can actively respond to and achieve the strategic goal of "carbon neutrality". In addition, the obtained polycarbonate also has excellent transparency and excellent barrier properties, and can be used as engineering plastics, disposable medicine and food packaging materials, adhesives, etc.
[0003] In 1969, Inoue used ZnEt 2 -H 2 O system catalyzes CO for the first time 2 With epoxide ring-opening copolymerization (ROCOP), a degradable polycarbonate material is prepared. Based on this, a variety of heterogeneous and homogeneous catalytic systems for this reaction have also been developed and studied. Heterogeneous catalytic systems such as alkyl zinc / active hydrogen catalytic systems, metal carboxylate systems, double metal cyanide catalysts, and rare earth ternary catalysts have the characteristics of being separable and recyclable, and the resulting polymer has a light color. They can be recycled many times in the reaction, effectively reducing costs, but due to their inherent heterogeneous reactions, further improvements in activity and selectivity are severely limited. Similarly, although homogeneous catalysts such as diimine zinc catalysts, metal porphyrin catalysts, and metal salen catalysts can break through the limitations of heterogeneous catalysts and achieve the advantages of high catalytic activity, high selectivity, and high stability, their inherent homogeneous reactions make it difficult for the catalyst to be separated from the polymer, and they are always faced with problems such as metal residues and affected polymer quality. At the same time, these catalysts have the disadvantages of insufficient activity, more cyclic byproducts during the polymerization process, and difficult control of the composition ratio of the polymer product.
[0004] In order to combine the high activity and high selectivity of homogeneous catalysts with the advantages of easy separation and recovery of heterogeneous catalysts, people have tried to make homogeneous catalysts heterogeneous and designed catalytic systems with complex microporous structures, such as metal organic frameworks (MOFs) and conjugated microporous polymers (CMPs). Although complete heterogeneity has been achieved, these catalysts do not perform well in polymer synthesis, and the advantages of homogeneous catalysts have been lost. At the same time, in order to further improve the activity and selectivity of epoxide and carbon dioxide copolymerization, people have introduced synergistic catalytic mechanisms into the design of catalytic systems. These include the multi-center metal synergy of bimetallic and multimetallic catalysts, the two-component catalytic system composed of SalenCo catalysts and quaternary ammonium salts or quaternary phosphonium salt co-catalysts, and the Lewis acid-base synergy of bifunctional catalysts. These catalytic systems can achieve polymerization at lower catalyst concentrations, and have significantly improved the control of the selective generation of polymers or carbonate segment content, but their homogeneous properties are still difficult to meet market demand. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a supported metal porphyrin complex, a preparation method and an application thereof. The supported metal porphyrin complex is used as a catalyst for preparing polycarbonate and exhibits high catalytic performance and good separation and recovery performance.
[0006] The present invention provides a supported metal porphyrin complex having a structure shown in Formula I:
[0007]
[0008] The carrier is selected from an inorganic carrier, a polymer carrier or a composite carrier of an inorganic carrier and a polymer carrier;
[0009] The inorganic carrier is selected from SiO 2 、Al 2 O 3 Or SiO2 functionalized with bromine, chloromethyl, carboxyl, amino, hydroxyl, or thiol 2 、Al 2 O 3 One or more of the following;
[0010] The polymer carrier is selected from one or more of cross-linked polystyrene, polyamide, polyethylene glycol resin, or cross-linked polystyrene, polyamide, or polyethylene glycol resin functionalized with bromide, chloromethyl, carboxyl, amino, hydroxyl, or thiol;
[0011] The Linker 1 is a linking group having a structure shown in Formula II-a or Formula II-b;
[0012]
[0013] The N or O atoms connected;
[0014] The Linker 2 is a linking group having a structure shown in Formula II-c:
[0015]
[0016] Where *′ is connected to R;
[0017] The range of x and y is 0 <x<100%,0≤y<100%;
[0018] The R is selected from dimethylamino, diethylamino, di-n-propylamino, diisopropylamino, diphenylamino, triethylammonium chloride, trihexylammonium chloride,
[0019] Said A metal porphyrin complex having a structure shown in formula III;
[0020]
[0021] The X is a halogen group, -NO 3 , CH 3 COO-、CCl 3 COO-, CF 3 COO-、ClO 4- , BF 4- BPh 4- 、-CN、-N 3 , p-toluene benzoate, p-toluene sulfonate, o-nitrophenolate anion, p-nitrophenolate anion, m-nitrophenolate anion, 2,4-dinitrophenolate anion, 3,5-dinitrophenolate anion, 2,4,6-trinitrophenolate anion, 3,5-dichlorophenolate anion, 3,5-difluorophenolate anion, 3,5-di-trifluoromethylphenolate anion or pentafluorophenolate anion;
[0022] R 1 ~R 19 are each independently selected from hydrogen, halogen, aliphatic, substituted aliphatic, substituted heteroaliphatic, aryl, substituted aryl or substituted heteroaryl;
[0023] M is magnesium, aluminum, zinc, chromium, manganese, iron, cobalt, titanium, yttrium, nickel or ruthenium.
[0024] Preferably, the carrier is selected from cross-linked polystyrene resin functionalized with chloromethyl.
[0025] Preferably, the Linker 1 is selected from Formula II-a:
[0026]
[0027] The N atom and connected.
[0028] Preferably, said R is selected from triethylammonium chloride.
[0029] Preferably, the metal porphyrin complex is specifically selected from the structure shown in formula III-a:
[0030]
[0031] In Formula III-a, R 20 Selected from hydrogen, halogen, C1-C10 aliphatic group, C1-C10 substituted alkoxy group, C3-C10 substituted cycloalkyl group, C1-C10 heterocyclic group, C6-C12 substituted aryl group or substituted C1-C12 heteroaryl group;
[0032] X 1 is selected from halogen;
[0033] M is aluminum, zinc, chromium, manganese, iron, cobalt, titanium, yttrium, nickel or ruthenium.
[0034] The present invention provides a method for preparing the supported metal porphyrin complex described in the above technical solution, comprising the following steps:
[0035] The porphyrin ligand having the structure of formula IV is reacted with an organic compound containing M and X groups to obtain a metal porphyrin complex having the structure of formula III;
[0036] The metal porphyrin complex and the tertiary amine monomer react with the functional group on the carrier to obtain a supported metal porphyrin complex having a structure of formula I;
[0037]
[0038] The M is magnesium, aluminum, zinc, chromium, manganese, iron, cobalt, titanium, yttrium, nickel or ruthenium;
[0039] The X is a halogen group, -NO 3 , CH 3 COO-、CCl 3 COO-, CF 3 COO-、ClO 4- , BF 4- BPh 4- 、-CN、-N 3, p-toluene benzoate, p-toluene sulfonate, o-nitrophenolate anion, p-nitrophenolate anion, m-nitrophenolate anion, 2,4-dinitrophenolate anion, 3,5-dinitrophenolate anion, 2,4,6-trinitrophenolate anion, 3,5-dichlorophenolate anion, 3,5-difluorophenolate anion, 3,5-di-trifluoromethylphenolate anion or pentafluorophenolate anion;
[0040] R 1 ~R 19 are independently selected from hydrogen, halogen, aliphatic, substituted aliphatic, substituted heteroaliphatic, aryl, substituted aryl or substituted heteroaryl.
[0041] The present invention also provides the use of the supported metal porphyrin complex as a catalyst in the preparation of polycarbonate.
[0042] The present invention also provides a method for preparing polycarbonate, comprising the following steps:
[0043] Under the catalytic action of the above-mentioned supported metal porphyrin complex, carbon dioxide and epoxide are copolymerized to obtain polycarbonate.
[0044] Preferably, the copolymerization temperature is 20-150° C., the copolymerization time is 8-72 h, the carbon dioxide pressure is 2-8 MPa, and the molar ratio of the supported metal porphyrin complex to the epoxide is 1:1000-50000.
[0045] Preferably, the epoxide is selected from one or more of ethylene oxide, propylene oxide, 1,2-butylene oxide, cyclohexene oxide, cyclopentane oxide, epichlorohydrin methacrylate glycidyl ether, methyl glycidyl ether, phenyl glycidyl ether and styrene alkylene oxide.
[0046] Beneficial effects of the present invention
[0047] The present invention provides a supported metal porphyrin complex and a preparation method and application thereof. The supported porphyrin complex is composed of a carrier, a linking group, an active component and an auxiliary agent chemically linked to the carrier, and has a structure shown in Formula I. The supported metal porphyrin catalyst is a heterogeneous catalyst, which is easy to separate from the system after the reaction, and can be recycled and reused, while reducing the metal residue in the polymer, which is more environmentally friendly.
[0048] The complex is prepared by loading a metal porphyrin complex and a quaternary ammonium salt monomer on a specific functionalized carrier. In the synthesis stage of the supported catalyst, supported metal porphyrin complexes with different loadings of the metal porphyrin complex and the tertiary amine monomer on the carrier can be synthesized by regulating the molar ratio of the functional groups, the metal porphyrin complex and the tertiary amine monomer on the carrier (1:2x:y, 0 < x < 100%, 0 ≤ y < 100%). In addition, supported metal porphyrin complexes with different catalytic performances can also be obtained by changing the metal center of the porphyrin monomer, the substituents of the porphyrin monomer, and the type of the quaternary ammonium salt monomer;
[0049] Compared with the prior art, the supported metal porphyrin complex can be further synthesized into a dual-component supported metal porphyrin complex, and both can be used as catalysts to efficiently catalyze the copolymerization reaction of carbon dioxide and epoxides to obtain polycarbonate products. The complex has a heterogeneous nature as a catalyst and is easy to separate from the reaction system after the reaction, realizing recycling and reuse; meanwhile, the catalyst simultaneously satisfies the multi-center metal synergistic effect and the Lewis acid-base synergistic effect between the metal porphyrin complex and the quaternary ammonium salt monomer. Their interaction can improve the catalytic performance by changing the metal center of the porphyrin monomer, the substituents of the porphyrin monomer, the loading of the porphyrin monomer, the type of the quaternary ammonium salt monomer and its loading. The catalyst shows high polymer selectivity, high carbonate content, high activity and high recovery rate after separation in the copolymerization of carbon dioxide and epoxides. Experimental results show that in the ring-opening copolymerization reaction of carbon dioxide and epoxides catalyzed by the catalyst, the number-average molecular weight of the product is 12,000 - 280,000 g / mol, and the molecular weight distribution is 1.01 - 2.61; the polymer selectivity in the reaction product can reach up to 99%, and the content of carbonate units can be regulated within a wide range of 0 - 95%. Description of the Drawings
[0050] Figure 1 It is the preparation reaction route diagram of complex EL1-3;
[0051] Figure 2 It is the preparation reaction route diagram of EC1;
[0052] Figure 3 It is the preparation reaction route diagram of EC2-6;
[0053] Figure 4 It is the preparation reaction route diagram of EC7-9;
[0054] Figure 5 It is the preparation reaction route diagram of EC10;
[0055] Figure 6 It is the preparation reaction route diagram of polycarbonate;
[0056] Figure 7 is the H NMR spectrum of complex EL-1;
[0057] Figure 8 is the H NMR spectrum of complex EL-3;
[0058] Fig. 9 This is the H NMR spectrum of EC-1. DETAILED DESCRIPTION
[0059] The present invention provides a supported metal porphyrin complex having a structure shown in Formula I:
[0060]
[0061] The carrier is a carrier selected from an inorganic carrier, a polymer carrier or a composite carrier of an inorganic carrier and a polymer carrier;
[0062] The inorganic carrier is selected from SiO 2 、Al 2 O 3 Or SiO2 functionalized with bromine, chloromethyl, carboxyl, amino, hydroxyl, or thiol 2 、Al 2 O 3 One or more of the following;
[0063] The polymer carrier is selected from one or more of cross-linked polystyrene, polyamide, polyethylene glycol resin or cross-linked polystyrene, polyamide or polyethylene glycol resin functionalized with bromide, chloromethyl, carboxyl, amino, hydroxyl or thiol; preferably, the carrier is selected from cross-linked polystyrene resin functionalized with chloromethyl.
[0064] The Linker 1 is a linker group having a structure shown in Formula II-a or Formula II-b, preferably a linker group having a structure shown in Formula II-a;
[0065]
[0066] The N or O atoms connected;
[0067] The Linker2 is a linking group having a structure shown in Formula II-c:
[0068]
[0069] Where *′ is connected to R;
[0070] The range of x and y is 0 <x<100%,0≤y<100%;
[0071] The R is selected from dimethylamino, diethylamino, di-n-propylamino, diisopropylamino, diphenylamino, triethylammonium chloride, trihexylammonium chloride, Preferably triethylammonium chloride;
[0072] Said It is a metal porphyrin complex having a structure shown in formula III:
[0073]
[0074] The X is a halogen group, -NO 3 , CH 3 COO-、CCl 3 COO-, CF 3 COO-、ClO 4- , BF 4- BPh 4- 、-CN、-N 3 , p-toluene benzoate, p-toluene sulfonate, o-nitrophenolate anion, p-nitrophenolate anion, m-nitrophenolate anion, 2,4-dinitrophenolate anion, 3,5-dinitrophenolate anion, 2,4,6-trinitrophenolate anion, 3,5-dichlorophenolate anion, 3,5-difluorophenolate anion, 3,5-di-trifluoromethylphenolate anion or pentafluorophenolate anion;
[0075] R 1 ~R 19 are each independently selected from hydrogen, halogen, aliphatic, substituted aliphatic, substituted heteroaliphatic, aryl, substituted aryl or substituted heteroaryl;
[0076] M is magnesium, aluminum, zinc, chromium, manganese, iron, cobalt, titanium, yttrium, nickel or ruthenium.
[0077] Preferably, the metal porphyrin complex is specifically selected from the structure shown in III-a:
[0078]
[0079] In Formula III-a, R 20 Selected from hydrogen, halogen, C1-C10 aliphatic group, C1-C10 substituted alkoxy group, C3-C10 substituted cycloalkyl group, C1-C10 heterocyclic group, C6-C12 substituted aryl group or substituted C1-C12 heteroaryl group; preferably hydrogen;
[0080] X 1 is selected from halogen, preferably Cl;
[0081] M is aluminum, zinc, chromium, manganese, iron, cobalt, titanium, yttrium, nickel or ruthenium, preferably aluminum.
[0082] Preferably, the supported metal porphyrin complex has a specific structure as shown in Formula V:
[0083]
[0084] In the present invention, the The preparation method is not particularly limited and can be commercially available or prepared according to methods well known to those skilled in the art;
[0085] The present invention The specific preparation method is:
[0086] Benzaldehyde and pyrrole are reacted in one pot under the condition of propionic acid reflux, and the first color band is collected by column chromatography separation technology to obtain tetraphenylporphyrin;
[0087] Tetraphenylporphyrin is dissolved in trifluoroacetic acid and reacted with sodium nitrite at room temperature to undergo nitration. After the reaction is completed, it is quenched with ice deionized water, the organic phase is neutralized with saturated sodium bicarbonate solution, and the organic phases are extracted and combined to obtain mononitro tetraphenylporphyrin;
[0088] Under nitrogen environment, mononitrotetraphenylporphyrin was dissolved in concentrated hydrochloric acid and subjected to reduction reaction with concentrated hydrochloric acid solution of stannous chloride at 65° C. After the reaction, concentrated ammonia was added to quench until the system was neutral, and the filter cake obtained by suction was collected by column chromatography separation technology to obtain monoaminoporphyrin.
[0089] The central metal M and the co-ligand X are coordinated to the porphyrin ring through the metalation reaction of the porphyrin ligand in a dichloromethane solution. The group accession method is: the amino group of the monoamino-substituted porphyrin reacts with the benzyl chloride group on the carrier under alkaline conditions to undergo a nucleophilic substitution reaction. According to the required loading rate, the ratio of the monoamino metal porphyrin to the benzyl chloride group on the carrier is regulated. Potassium carbonate is used as an acid binding agent. Specifically, the molar ratio between the benzyl chloride group on the carrier, the monoamino porphyrin and potassium carbonate is 1:2x:x. The carrier and the monoamino metal porphyrin are fully swollen or dissolved in anhydrous N,N-dimethylformamide (DMF) and fully reacted at 90°C for 72 hours. The R group accession method is: after the above metal porphyrin complex is loaded on the carrier, a tertiary amine monomer is further added in an equal molar amount to the benzyl chloride group in the carrier, anhydrous DMF is used as a solvent, and fully reacted at 90°C for 24 hours.
[0090] The present invention provides a method for preparing the supported metal porphyrin complex described in the above technical solution, comprising the following steps:
[0091] A porphyrin ligand having a structure of formula IV is reacted with an organic compound containing M and X groups to obtain a metal porphyrin complex having a structure of formula III; the organic compound containing M and X groups is preferably diethylaluminum chloride, the reaction temperature is preferably room temperature (25° C.), the reaction time is preferably 2 hours, and the molar ratio of the porphyrin ligand having a structure of formula IV to the organic compound containing M and X groups is preferably 1:1.2.
[0092] The metal porphyrin complex and the tertiary amine monomer react with the functional groups on the carrier to obtain a supported metal porphyrin complex having a structure of formula I; the tertiary amine monomer is preferably triethylamine, the reaction temperature is preferably 90° C., the reaction time is preferably 72-100 hours, and the molar amounts of the corresponding metal porphyrin complex and the tertiary amine monomer are calculated according to the molar amount of the functional groups on a certain mass of the carrier, wherein the molar ratio of the functional groups on the carrier added, the metal porphyrin complex and the tertiary amine monomer is 1:2x:y, wherein 0 <x<100%,0≤y<100%。
[0093]
[0094] The M is magnesium, aluminum, zinc, chromium, manganese, iron, cobalt, titanium, yttrium, nickel or ruthenium;
[0095] The X is a halogen group, -NO 3 , CH 3 COO-、CCl 3 COO-, CF 3 COO-、ClO 4- , BF 4- BPh 4- 、-CN、-N 3 , p-toluene benzoate, p-toluene sulfonate, o-nitrophenolate anion, p-nitrophenolate anion, m-nitrophenolate anion, 2,4-dinitrophenolate anion, 3,5-dinitrophenolate anion, 2,4,6-trinitrophenolate anion, 3,5-dichlorophenolate anion, 3,5-difluorophenolate anion, 3,5-di-trifluoromethylphenolate anion or pentafluorophenolate anion;
[0096] R 1 ~R 19 Independently selected from hydrogen, halogen, aliphatic, substituted aliphatic, substituted heteroaliphatic, aryl, substituted aryl or substituted heteroaryl, preferably hydrogen.
[0097] The present invention also provides the use of the above-mentioned supported metal porphyrin complex as a catalyst in the preparation of polycarbonate, comprising the following steps:
[0098] Under the catalysis of the above-mentioned supported metal porphyrin complex, carbon dioxide and epoxide are copolymerized to obtain polycarbonate;
[0099] In the present invention, the epoxide is selected from one or more of ethylene oxide, propylene oxide, 1,2-butylene oxide, cyclohexene oxide, cyclopentane oxide, epichlorohydrin methacrylate glycidyl ether, methyl glycidyl ether, phenyl glycidyl ether and styrene alkylene oxide.
[0100] In the present invention, the pressure of the carbon dioxide is preferably 2 to 8 MPa.
[0101] In the present invention, the copolymerization reaction temperature is preferably 20 to 150° C. A higher polymer selectivity (>99%) can be achieved at a lower temperature, and the reaction activity increases with increasing temperature. The copolymerization reaction time is preferably 8 to 72 hours.
[0102] In the present invention, the molar ratio of the supported metal porphyrin complex to the epoxide is preferably 1:1000-50000.
[0103] In the present invention, the supported metal porphyrin complex can prepare polycarbonate materials by catalyzing porphyrin and tertiary amine on the same polymer chain with high activity. After the reaction is completed, the catalyst can be separated from the reaction system to achieve recycling and reuse.
[0104] In order to further illustrate the present invention, a supported metal porphyrin complex and a preparation method thereof and a preparation method of polycarbonate provided by the present invention are described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.
[0105] Example 1 Preparation of Metalloporphyrin Complex
[0106] 50 g (470 mmol) of benzaldehyde and 31 g (470 mmol) of pyrrole were added to 500 mL of propionic acid, heated to about 130 °C, and refluxed for 1.5 h. After the reaction was completed, the reaction solution was cooled to room temperature, concentrated to 200 mL, and methanol was added and cooled in a refrigerator overnight. The product was filtered and purified by silica gel column chromatography (CHCl 3 / CH 3 The product EL1 was purified by 4% hydroxyethyl ester (EI) with a yield of about 20%. 1 H-NMR (CDCl 3 ,ppm):8.9,8.2,7.8,-2.8, such as Figure 7 As shown, high-resolution electrospray ionization mass spectrometry analysis showed that [C 44 H 31 N 4 ]:615.2,found:615.2;
[0107] Dissolve 1g (1.63mmol) EL1 in 10mL (1.63mmol) trifluoroacetic acid, add 0.2g (2.93mmol) sodium nitrite, stir well and react the mixture at room temperature for 3min. After the reaction is completed, add 50-100mL ice deionized water to quench, add 50mL chloroform to dilute and extract until the water phase is colorless, combine the organic phases, extract and wash three times with saturated sodium bicarbonate solution, and dry to obtain the product EL2. Under nitrogen environment, dissolve the dried EL2 in 20mL concentrated hydrochloric acid, prepare 1.44g (7.58mmol) stannous chloride and dissolve it in concentrated hydrochloric acid, stir well and add concentrated hydrochloric acid solution of stannous chloride to EL2, and react at 65℃ for 1h. After the reaction is completed, add concentrated ammonia to quench the reaction system to neutrality, filter with suction, wash the filter cake with deionized water three times and dry. The solid product was purified by silica gel column using dichloromethane as the eluent to obtain about 0.43 g of product EL3. 1 H-NMR (CDCl 3 , ppm): 8.9, 8.2, 8.0, 7.8, 7.0, 4.0, -2.8. High-resolution electrospray ionization mass spectrometry analysis showed that [C 44 H 31 N 5 ]:629.77,found:629.26。 The above reaction route schematic diagram is shown in Figure 1 ; NMR hydrogen spectrum as Figure 8 shown.
[0108] Under nitrogen protection, 0.4 g EL3 (0.64 mmol) of the above ligand was dissolved in dichloromethane, and 0.4 mL AlEt 2 Cl (diethylaluminum chloride) (2 mol / L, 0.77 mmol), stirred at room temperature for 2 h. The obtained product was purified by column chromatography and then dried to obtain the desired complex EC1.
[0109] Figure 2 The reaction route for the preparation of EC1 is shown in the H NMR spectrum. Fig. 9 shown.
[0110] Example 2 Preparation of supported metal porphyrin complex
[0111] Under nitrogen protection, 0.5 g of cross-linked polystyrene resin (Merrifield resin) (DVB: 1%, Cl: 0.8-1.3 mmol / g) was fully swollen in 10 mL of anhydrous DMF at 70°C for 24 h. 0.5 g (0.7 mmol) of EC1 was fully dissolved in 10 mL of anhydrous DMF and added to the swollen cross-linked polystyrene resin. K 2 CO3 35 mg (0.25 mmol), the temperature was raised to 90 ° C, and the reaction was continued for 72 hours. After the reaction was completed, the filter cake was filtered repeatedly with anhydrous DMF, anhydrous chloroform, and anhydrous dichloromethane until the filtrate was colorless and then dried to obtain the desired complex EC2. ICP analysis showed that x was 53.8%, y = 0. The preparation reaction route is shown in the figure Figure 3 shown.
[0112] Example 3 Preparation of supported metal porphyrin complex
[0113] Under nitrogen protection, 1 g of cross-linked polystyrene resin (Merrifield resin) (DVB: 1%, Cl: 0.8-1.3 mmol / g) was fully swollen in 10 mL of anhydrous DMF at 70°C for 24 h. 1 g (1.4 mmol) of EC1 was fully dissolved in 10 mL of anhydrous DMF and added to the swollen cross-linked polystyrene resin. K 2 CO 3 76 mg (0.55 mmol), the temperature was raised to 90 ° C, and the reaction was continued for 72 hours. After the reaction was completed, the filter cake was filtered repeatedly with anhydrous DMF, anhydrous chloroform, and anhydrous dichloromethane until the filtrate was colorless and then dried to obtain the desired complex EC3. ICP analysis showed that x was 20.6% and y = 0. The preparation reaction route is shown in the figure Figure 3 shown.
[0114] Example 4 Preparation of supported metal porphyrin complex
[0115] Under nitrogen protection, 2 g of cross-linked polystyrene resin (Merrifield resin) (DVB: 1%, Cl: 0.8-1.3 mmol / g) was fully swollen in 20 mL of anhydrous DMF at 70°C for 24 h. 1 g (1.4 mmol) of EC1 was fully dissolved in 10 mL of anhydrous DMF and added to the swollen cross-linked polystyrene resin. K 2 CO 3 87 mg (0.62 mmol), the temperature was raised to 90 ° C, and the reaction was continued for 72 hours. After the reaction was completed, the filter cake was filtered repeatedly with anhydrous DMF, anhydrous chloroform, and anhydrous dichloromethane until the filtrate was colorless and then dried to obtain the desired complex EC4. ICP analysis showed that x was 18.0%, y = 0. The preparation reaction route is shown in the figure Figure 3 shown.
[0116] Example 5 Preparation of supported metal porphyrin complex
[0117] Under nitrogen protection, 2 g of cross-linked polystyrene resin (Merrifield resin) (DVB: 1%, Cl: 0.8-1.3 mmol / g) was fully swollen in 10 mL of anhydrous DMF at 70°C for 24 h. 0.5 g (0.7 mmol) of EC1 was fully dissolved in 10 mL of anhydrous DMF and added to the swollen cross-linked polystyrene resin. K 2 CO 3 29 mg (0.21 mmol), the temperature was raised to 90 ° C, and the reaction was continued for 72 hours. After the reaction was completed, the filter cake was filtered repeatedly with anhydrous DMF, anhydrous chloroform, and anhydrous dichloromethane until the filtrate was colorless and then dried to obtain the desired complex EC5. ICP analysis showed that x was 4.38%, y = 0. The preparation reaction route is shown in the figure Figure 3 shown.
[0118] Example 6 Preparation of supported metal porphyrin complex
[0119] Under nitrogen protection, 2 g of cross-linked polystyrene resin (Merrifield resin) (DVB: 1%, Cl: 0.8-1.3 mmol / g) was fully swollen in 10 mL of anhydrous DMF at 70°C for 24 h. 3 g (4.3 mmol) of EC1 was fully dissolved in 10 mL of anhydrous DMF and added to the swollen cross-linked polystyrene resin. K 2 CO 3 69 mg (0.5 mmol), the temperature was raised to 90 ° C, and the reaction was continued for 72 hours. After the reaction was completed, the filter cake was filtered and washed repeatedly with anhydrous DMF, anhydrous chloroform, and anhydrous dichloromethane until the filtrate was colorless and then dried to obtain the desired complex EC6. ICP analysis showed that x was 44.6% and y = 0. The preparation reaction route is shown in the figure Figure 3 shown.
[0120] Example 7 Preparation of a two-component supported metal porphyrin complex
[0121] Under nitrogen protection, 0.8 g EC4 was fully swollen in 8 mL anhydrous DMF, and 0.1 g (1 mmol) triethylamine (NEt 3 ), react at 90°C for 24h. After the reaction is completed, suction filtration is performed, and the filter cake is repeatedly washed with anhydrous DMF, anhydrous chloroform, and anhydrous dichloromethane until the filtrate is colorless and then dried to obtain the desired complex EC7. By ICP analysis, x can be calculated to be 18.0% and y to be 82.0%. The preparation reaction route is shown in the figure Figure 4 shown.
[0122] Example 8 Preparation of a two-component supported metal porphyrin complex
[0123] Under nitrogen protection, 0.8 g of EC5 was fully swollen in 8 mL of anhydrous DMF, and 0.1 g (1 mmol) of triethylamine (NEt 3 ), react at 90°C for 24h. After the reaction is completed, suction filtration is performed, and the filter cake is repeatedly washed with anhydrous DMF, anhydrous chloroform, and anhydrous dichloromethane until the filtrate is colorless and then dried to obtain the desired complex EC8. By ICP analysis, x can be calculated to be 4.38% and y to be 95.6%. The preparation reaction route is shown in the figure Figure 4 shown.
[0124] Example 9 Preparation of a two-component supported metal porphyrin complex
[0125] Under nitrogen protection, 0.5 g of EC6 was fully swollen in 8 mL of anhydrous DMF, and 0.5 g (0.5 mmol) of triethylamine (NEt 3 ), react at 90°C for 24h. After the reaction, suction filtration was performed, and the filter cake was repeatedly washed with anhydrous DMF, anhydrous chloroform, and anhydrous dichloromethane until the filtrate was colorless and then dried to obtain the desired complex EC9. ICP analysis showed that x was 44.6% and y was 55.4%. The preparation reaction route is shown in Figure 4 shown.
[0126] Example 10 Preparation of a two-component supported metal porphyrin complex
[0127] Under nitrogen protection, 0.5 g EC6 was fully swollen in 8 mL anhydrous DMF, and 0.13 g (0.5 mmol) trihexylamine (N(C 6 H 13 ) 3 ), react at 90°C for 24h. After the reaction is completed, suction filtration is performed, and the filter cake is repeatedly washed with anhydrous DMF, anhydrous chloroform, and anhydrous dichloromethane until the filtrate is colorless and then dried to obtain the desired complex EC10. By ICP analysis, x can be calculated to be 44.6% and y to be 55.4%. The preparation reaction route is shown in the figure Figure 5 shown.
[0128] Example 11 Preparation of polycarbonate
[0129] In a glove box, 0.015 mmol (calculated according to the aluminum content in the resin) of the aluminum porphyrin complex EC2 in Example 2 and 75 mmol of dried propylene oxide were added to a 5 mL autoclave after dehydration and deoxygenation, and then the autoclave was taken out of the glove box, and carbon dioxide was filled into the autoclave through a carbon dioxide supply line with a pressure regulating function, so that the pressure in the autoclave reached 3 MPa, and the temperature of the autoclave was controlled at 70°C to carry out polymerization reaction for 24 hours. After the polymerization reaction was completed, the carbon dioxide in the autoclave was slowly discharged, and the autoclave was opened and taken as soon as possible. 1 The H-NMR sample was subjected to nuclear magnetic measurement. The unreacted propylene oxide was removed in a vacuum drying oven at 45°C to obtain a polycarbonate wrapped with a catalyst.
[0130] The polymer was fully dissolved in 10 mL of dichloromethane, and the insoluble matter was the catalyst. The solid-liquid separation was performed by extraction, and the solid part was repeatedly washed with acetone until the solids were dispersed with each other and there was no obvious polymer wrapped in them. After recovery, it was used as catalyst EC2 1 Used to catalyze new polymerization reactions; after the liquid portion is collected, it is dripped into methanol drop by drop, and light-colored or white polycarbonate gradually precipitates.
[0131] pass 1 The polycarbonate prepared in Example 11 was tested by H-NMR. The results showed that the carbonate unit content in the polycarbonate was 59% and the polymer selectivity was 84%. The TOF value of the catalytic system was calculated to be 140h -1 ; The number average molecular weight of the prepared polycarbonate measured by GPC is 43600 g / mol, and the molecular weight distribution is 1.61. The preparation reaction route is as follows Figure 6 shown.
[0132] Example 12 Preparation of polycarbonate
[0133] In a glove box, 0.015 mmol (calculated according to the aluminum content in the resin) of the aluminum porphyrin complex EC3 in Example 3 and 75 mmol of dried propylene oxide were added to a 5 mL autoclave after dehydration and deoxygenation, and then the autoclave was taken out of the glove box, and carbon dioxide was filled into the autoclave through a carbon dioxide supply line with a pressure regulating function, so that the pressure in the autoclave reached 3 MPa, and the temperature of the autoclave was controlled at 70°C to carry out polymerization reaction for 24 hours. After the polymerization reaction was completed, the carbon dioxide in the autoclave was slowly discharged, and the autoclave was opened and taken as soon as possible. 1 The H-NMR sample was subjected to nuclear magnetic measurement. The unreacted propylene oxide was removed in a vacuum drying oven at 45°C to obtain a polycarbonate wrapped with a catalyst.
[0134] The polymer was fully dissolved in 10 mL of dichloromethane, and the insoluble matter was the catalyst. The solid-liquid separation was performed by extraction, and the solid part was repeatedly washed with acetone until the solids were dispersed with each other and no obvious polymer was wrapped in them. After recovery, it was used as the catalyst EC3 1 Used to catalyze new polymerization reactions; after the liquid portion is collected, it is dripped into methanol drop by drop, and light-colored or white polycarbonate gradually precipitates.
[0135] pass 1 The polycarbonate prepared in Example 12 was tested by H-NMR. The results showed that the carbonate unit content in the polycarbonate was 67% and the polymer selectivity was 82%. The TOF value of the catalytic system was calculated to be 40h -1 ; The number average molecular weight of the prepared polycarbonate measured by GPC is 21600 g / mol, and the molecular weight distribution is 1.27. The preparation reaction route is as follows Figure 6 shown.
[0136] Example 13 Preparation of polycarbonate
[0137] In a glove box, 0.015 mmol (calculated according to the aluminum content in the resin) of the aluminum porphyrin complex EC4 in Example 4 and 75 mmol of dried propylene oxide were added to a 5 mL autoclave after dehydration and deoxygenation, and then the autoclave was taken out of the glove box, and carbon dioxide was filled into the autoclave through a carbon dioxide supply line with a pressure regulating function, so that the pressure in the autoclave reached 3 MPa, and the temperature of the autoclave was controlled at 70°C to carry out polymerization reaction for 24 hours. After the polymerization reaction was completed, the carbon dioxide in the autoclave was slowly discharged, and the autoclave was opened and taken as soon as possible. 1 The H-NMR sample was subjected to nuclear magnetic measurement. The unreacted propylene oxide was removed in a vacuum drying oven at 45°C to obtain a polycarbonate wrapped with a catalyst.
[0138] The polymer was fully dissolved in 10 mL of dichloromethane, and the insoluble matter was the catalyst. The solid-liquid separation was performed by extraction, and the solid part was repeatedly washed with acetone until the solids were dispersed with each other and no obvious polymer was wrapped in them. After recovery, it was used as catalyst EC4 1 Used to catalyze new polymerization reactions; after the liquid portion is collected, it is dripped into methanol drop by drop, and light-colored or white polycarbonate gradually precipitates.
[0139] pass 1 The polycarbonate prepared in Example 13 was tested by H-NMR. The results showed that the carbonate unit content in the polycarbonate was 77% and the polymer selectivity was 87%. The TOF value of the catalytic system was calculated to be 30h -1; The number average molecular weight of the prepared polycarbonate measured by GPC is 25100 g / mol, and the molecular weight distribution is 1.91. The preparation reaction route is as follows Figure 6 shown.
[0140] Example 14 Preparation of polycarbonate
[0141] In a glove box, 0.015 mmol (calculated according to the aluminum content in the resin) of the aluminum porphyrin complex EC5 in Example 5 and 75 mmol of dried propylene oxide were added to a 5 mL autoclave after dehydration and deoxygenation, and then the autoclave was taken out of the glove box, and carbon dioxide was filled into the autoclave through a carbon dioxide supply line with a pressure regulating function to make the pressure in the autoclave reach 3 MPa, and the temperature of the autoclave was controlled at 70°C to carry out polymerization reaction for 24 hours. After the polymerization reaction was completed, the carbon dioxide in the autoclave was slowly discharged, and the autoclave was opened and taken as soon as possible. 1 The H-NMR sample was subjected to nuclear magnetic measurement. The unreacted propylene oxide was removed in a vacuum drying oven at 45°C to obtain a polycarbonate wrapped with a catalyst.
[0142] The polymer was fully dissolved in 10 mL of dichloromethane, and the insoluble matter was the catalyst. The solid-liquid separation was performed by extraction. The solid part was repeatedly washed with acetone until the solids were dispersed with each other and there was no obvious polymer wrapped in them. After recovery, it was used as the catalyst EC5 1 Used to catalyze new polymerization reactions; after the liquid portion is collected, it is dripped into methanol drop by drop, and light-colored or white polycarbonate gradually precipitates.
[0143] pass 1 The polycarbonate prepared in Example 14 was tested by H-NMR. The results showed that the carbonate unit content in the polycarbonate was 95% and the polymer selectivity was 79%. The TOF value of the catalytic system was calculated to be 71h -1 ; The number average molecular weight of the prepared polycarbonate measured by GPC is 21400 g / mol, and the molecular weight distribution is 1.17. The preparation reaction route is as follows Figure 6 shown.
[0144] Example 15 Preparation of polycarbonate
[0145] In a glove box, 0.015 mmol (calculated according to the aluminum content in the resin) of the aluminum porphyrin complex EC6 in Example 6 and 75 mmol of dried propylene oxide were added to a 5 mL autoclave after dehydration and deoxygenation, and then the autoclave was taken out of the glove box, and carbon dioxide was filled into the autoclave through a carbon dioxide supply line with a pressure regulating function to make the pressure in the autoclave reach 3 MPa, and the temperature of the autoclave was controlled at 70°C to carry out polymerization reaction for 24 hours. After the polymerization reaction was completed, the carbon dioxide in the autoclave was slowly discharged, and the autoclave was opened and taken as soon as possible. 1 The H-NMR sample was subjected to nuclear magnetic measurement. The unreacted propylene oxide was removed in a vacuum drying oven at 45°C to obtain a polycarbonate wrapped with a catalyst.
[0146] The polymer was fully dissolved in 10 mL of dichloromethane, and the insoluble matter was the catalyst. The solid-liquid separation was performed by extraction, and the solid part was repeatedly washed with acetone until the solids were dispersed with each other and there was no obvious polymer wrapped in them. After recovery, it was used as catalyst EC6 1 Used to catalyze new polymerization reactions; after the liquid portion is collected, it is dripped into methanol drop by drop, and light-colored or white polycarbonate gradually precipitates.
[0147] pass 1 The polycarbonate prepared in Example 15 was tested by H-NMR. The results showed that the carbonate unit content in the polycarbonate was 51% and the polymer selectivity was 90%. The TOF value of the catalytic system was calculated to be 72h -1 ; The number average molecular weight of the prepared polycarbonate measured by GPC is 47700 g / mol, and the molecular weight distribution is 1.71. The preparation reaction route is as follows Figure 6 shown.
[0148] Example 16 Preparation of polycarbonate
[0149] In a glove box, 0.015 mmol (calculated according to the aluminum content in the resin) of the aluminum porphyrin complex EC7 in Example 4 and 7 mmol of dried propylene oxide were added to a 5 mL autoclave after dehydration and deoxygenation, and then the autoclave was taken out of the glove box, and carbon dioxide was filled into the autoclave through a carbon dioxide supply line with a pressure regulating function to make the pressure in the autoclave reach 3 MPa, and the temperature of the autoclave was controlled at 70°C to carry out polymerization reaction for 24 hours. After the polymerization reaction was completed, the carbon dioxide in the autoclave was slowly discharged, and the autoclave was opened and taken as soon as possible. 1 The H-NMR sample was subjected to nuclear magnetic measurement. The unreacted propylene oxide was removed in a vacuum drying oven at 45°C to obtain a polycarbonate wrapped with a catalyst.
[0150] The polymer was fully dissolved in 10 mL of dichloromethane, and the insoluble matter was the catalyst. The solid-liquid separation was performed by extraction, and the solid part was repeatedly washed with acetone until the solids were dispersed with each other and there was no obvious polymer wrapped in them. After recovery, it was used as the catalyst EC7 1 Used to catalyze new polymerization reactions; after the liquid portion is collected, it is dripped into methanol drop by drop, and light-colored or white polycarbonate gradually precipitates.
[0151] pass 1 The polycarbonate prepared in Example 16 was tested by H-NMR. The results showed that the carbonate unit content in the polycarbonate was 92% and the polymer selectivity was 46%. The TOF value of the catalytic system was calculated to be 139h -1 ; The number average molecular weight of the prepared polycarbonate measured by GPC is 13200 g / mol, and the molecular weight distribution is 1.97. The preparation reaction route is as follows Figure 6 shown.
[0152] Example 17 Preparation of polycarbonate
[0153] In a glove box, 0.015 mmol (calculated according to the aluminum content in the resin) of the aluminum porphyrin complex EC8 in Example 5 and 210 mmol of dried propylene oxide were added to a 5 mL autoclave after dehydration and deoxygenation, and then the autoclave was taken out of the glove box, and carbon dioxide was filled into the autoclave through a carbon dioxide supply line with a pressure regulating function to make the pressure in the autoclave reach 3 MPa, and the temperature of the autoclave was controlled at 70°C to carry out polymerization reaction for 24 hours. After the polymerization reaction was completed, the carbon dioxide in the autoclave was slowly discharged, and the autoclave was opened and taken as soon as possible. 1 H-NMR nuclear magnetic sample, and perform nuclear magnetic measurement.
[0154] The reaction system was separated into solid and liquid, and the solid part was repeatedly washed with dichloromethane or acetone for 3 times and then used as catalyst EC8 1 Recycling is carried out for new polymerization reactions.
[0155] pass 1 The product obtained in Example 17 was tested by H-NMR. The results showed that PO had been completely converted into cyclic carbonate. The TOF value of the catalytic system was calculated to be 583 h -1 The preparation reaction route is as follows Figure 6 shown.
[0156] Example 18 Preparation of polycarbonate
[0157] In a glove box, 0.015 mmol (calculated according to the aluminum content in the resin) of the aluminum porphyrin complex EC9 in Example 6 and 75 mmol of dried propylene oxide were added to a 5 mL autoclave after dehydration and deoxygenation, and then the autoclave was taken out of the glove box, and carbon dioxide was filled into the autoclave through a carbon dioxide supply line with a pressure regulating function to make the pressure in the autoclave reach 3 MPa, and the temperature of the autoclave was controlled at 70°C to carry out polymerization reaction for 24 hours. After the polymerization reaction was completed, the carbon dioxide in the autoclave was slowly discharged, and the autoclave was opened and taken as soon as possible. 1 The H-NMR sample was subjected to nuclear magnetic measurement. The unreacted propylene oxide was removed in a vacuum drying oven at 45°C to obtain a polycarbonate wrapped with a catalyst.
[0158] The polymer was fully dissolved in 10 mL of dichloromethane, and the insoluble matter was the catalyst. The solid-liquid separation was performed by extraction, and the solid part was repeatedly washed with acetone until the solids were dispersed with each other and there was no obvious polymer wrapped in them. After recovery, it was used as the catalyst EC9 1 Used to catalyze new polymerization reactions; after the liquid portion is collected, it is dripped into methanol drop by drop, and light-colored or white polycarbonate gradually precipitates.
[0159] pass 1 The polycarbonate prepared in Example 18 was tested by H-NMR. The results showed that the carbonate unit content in the polycarbonate was 65% and the polymer selectivity was 94%. The TOF value of the catalytic system was calculated to be 97h -1 ; The number average molecular weight of the prepared polycarbonate measured by GPC is 64000 g / mol, and the molecular weight distribution is 1.47. The preparation reaction route is as follows Figure 6 shown.
[0160] Example 19 Preparation of polycarbonate
[0161] In a glove box, 0.015 mmol (calculated according to the aluminum content in the resin) of the aluminum porphyrin complex EC6 in Example 6 and 75 mmol of dried propylene oxide were added to a 5 mL autoclave after dehydration and deoxygenation, and then the autoclave was taken out of the glove box, and carbon dioxide was filled into the autoclave through a carbon dioxide supply line with a pressure regulating function to make the pressure in the autoclave reach 3 MPa, and the temperature of the autoclave was controlled at 50°C to carry out polymerization reaction for 24 hours. After the polymerization reaction was completed, the carbon dioxide in the autoclave was slowly discharged, and the autoclave was opened and taken as soon as possible. 1 The H-NMR sample was subjected to nuclear magnetic measurement. The unreacted propylene oxide was removed in a vacuum drying oven at 45°C to obtain a polycarbonate wrapped with a catalyst.
[0162] The polymer was fully dissolved in 10 mL of dichloromethane, and the insoluble matter was the catalyst. The solid-liquid separation was performed by extraction, and the solid part was repeatedly washed with acetone until the solids were dispersed with each other and there was no obvious polymer wrapped in them. After recovery, it was used as catalyst EC6 1 Used to catalyze new polymerization reactions; after the liquid portion is collected, it is dripped into methanol drop by drop, and light-colored or white polycarbonate gradually precipitates.
[0163] pass 1 The polycarbonate prepared in Example 19 was tested by H-NMR. The results showed that the carbonate unit content in the polycarbonate was 42% and the polymer selectivity was greater than 99%. The TOF value of the catalytic system was calculated to be 15h -1 ; The number average molecular weight of the prepared polycarbonate measured by GPC is 26600 g / mol, and the molecular weight distribution is 1.32. The preparation reaction route is as follows Figure 6 shown.
[0164] Example 20 Preparation of polycarbonate
[0165] In a glove box, 0.015mmol (calculated according to the aluminum content in the resin) of the aluminum porphyrin complex EC6 in Example 6, 0.0075mmol PPNCl and 75mmol of dry propylene oxide were added to a 5mL autoclave after dehydration and deoxygenation, and then the autoclave was taken out of the glove box, and carbon dioxide was filled into the autoclave through a carbon dioxide supply line with a pressure regulating function, so that the pressure in the autoclave reached 3MPa, and the temperature of the autoclave was controlled at 70°C to carry out polymerization reaction for 24h. After the polymerization reaction was completed, the carbon dioxide in the autoclave was slowly discharged, and the autoclave was opened and taken as soon as possible. 1 The H-NMR sample was subjected to nuclear magnetic measurement. The unreacted propylene oxide was removed in a vacuum drying oven at 45°C to obtain a polycarbonate wrapped with a catalyst.
[0166] The polymer was fully dissolved in 10 mL of dichloromethane, and the insoluble matter was the catalyst. The solid-liquid separation was performed by extraction, and the solid part was repeatedly washed with acetone until the solids were dispersed with each other and there was no obvious polymer wrapped in them. After recovery, it was used as catalyst EC6 1 Used to catalyze new polymerization reactions; after the liquid portion is collected, it is dripped into methanol drop by drop, and light-colored or white polycarbonate gradually precipitates.
[0167] pass 1 The polycarbonate prepared in Example 20 was tested by H-NMR. The results showed that the carbonate unit content in the polycarbonate was 51% and the polymer selectivity was greater than 76%. The TOF value of the catalytic system was calculated to be 72h -1; The number average molecular weight of the prepared polycarbonate measured by GPC is 39500 g / mol, and the molecular weight distribution is 1.65. The preparation reaction route is as follows Figure 6 shown.
[0168] Example 21 Preparation of polycarbonate
[0169] In a glove box, 0.015 mmol (calculated according to the aluminum content in the resin) of the aluminum porphyrin complex EC5 in Example 5 and 210 mmol of dried propylene oxide were added to a 5 mL autoclave after dehydration and deoxygenation, and then the autoclave was taken out of the glove box, and carbon dioxide was filled into the autoclave through a carbon dioxide supply line with a pressure regulating function to make the pressure in the autoclave reach 3 MPa, and the temperature of the autoclave was controlled at 70°C to carry out polymerization reaction for 24 hours. After the polymerization reaction was completed, the carbon dioxide in the autoclave was slowly discharged, and the autoclave was opened and taken as soon as possible. 1 The H-NMR sample was subjected to nuclear magnetic measurement. The unreacted propylene oxide was removed in a vacuum drying oven at 45°C to obtain a polycarbonate wrapped with a catalyst.
[0170] The polymer was fully dissolved in 10 mL of dichloromethane, and the insoluble matter was the catalyst. The solid-liquid separation was performed by extraction. The solid part was repeatedly washed with acetone until the solids were dispersed with each other and there was no obvious polymer wrapped in them. After recovery, it was used as the catalyst EC5 1 Used to catalyze new polymerization reactions; after the liquid portion is collected, it is dripped into methanol drop by drop, and light-colored or white polycarbonate gradually precipitates.
[0171] pass 1 The polycarbonate prepared in Example 21 was tested by H-NMR. The results showed that the carbonate unit content in the polycarbonate was 80% and the polymer selectivity was 44%. The TOF value of the catalytic system was calculated to be 90h -1 ; The number average molecular weight of the prepared polycarbonate measured by GPC is 5300 g / mol, and the molecular weight distribution is 3.38. The preparation reaction route is as follows Figure 6 shown.
[0172] Example 22 Preparation of polycarbonate
[0173] In a glove box, 0.015 mmol (calculated according to the aluminum content in the resin) of the aluminum porphyrin complex EC5 in Example 5 of the preparation of polycarbonate and 420 mmol of dried propylene oxide were added to a 5 mL autoclave after dehydration and deoxygenation, and then the autoclave was taken out of the glove box, and carbon dioxide was filled into the autoclave through a carbon dioxide supply line with a pressure regulating function, so that the pressure in the autoclave reached 3 MPa, and the temperature of the autoclave was controlled at 70°C to carry out polymerization reaction for 24 hours. After the polymerization reaction was completed, the carbon dioxide in the autoclave was slowly discharged, and the autoclave was opened and taken as soon as possible. 1 The H-NMR sample was subjected to nuclear magnetic measurement. The unreacted propylene oxide was removed in a vacuum drying oven at 45°C to obtain a polycarbonate wrapped with a catalyst.
[0174] The polymer was fully dissolved in 10 mL of dichloromethane, and the insoluble matter was the catalyst. The solid-liquid separation was performed by extraction. The solid part was repeatedly washed with acetone until the solids were dispersed with each other and there was no obvious polymer wrapped in them. After recovery, it was used as the catalyst EC5 1 Used to catalyze new polymerization reactions; after the liquid portion is collected, it is dripped into methanol drop by drop, and light-colored or white polycarbonate gradually precipitates.
[0175] pass 1 The polycarbonate prepared in Example 22 was tested by H-NMR. The results showed that the carbonate unit content in the polycarbonate was 94% and the polymer selectivity was 62%. The TOF value of the catalytic system was calculated to be 76h -1 ; The number average molecular weight of the prepared polycarbonate measured by GPC is 3400 g / mol, and the molecular weight distribution is 2.13. The preparation reaction route is as follows Figure 6 shown.
[0176] Example 23 Preparation of polycarbonate
[0177] In a glove box, 0.015 mmol (calculated according to the aluminum content in the resin) of the aluminum porphyrin complex EC5 in Example 5 and 150 mmol of dried propylene oxide were added to a 5 mL autoclave after dehydration and deoxygenation, and then the autoclave was taken out of the glove box, and carbon dioxide was filled into the autoclave through a carbon dioxide supply line with a pressure regulating function to make the pressure in the autoclave reach 3 MPa, and the temperature of the autoclave was controlled at 70°C to carry out polymerization reaction for 24 hours. After the polymerization reaction was completed, the carbon dioxide in the autoclave was slowly discharged, and the autoclave was opened and taken as soon as possible. 1 The H-NMR sample was subjected to nuclear magnetic measurement. The unreacted propylene oxide was removed in a vacuum drying oven at 45°C to obtain a polycarbonate wrapped with a catalyst.
[0178] The polymer was fully dissolved in 10 mL of dichloromethane, and the insoluble matter was the catalyst. The solid-liquid separation was performed by extraction. The solid part was repeatedly washed with acetone until the solids were dispersed with each other and there was no obvious polymer wrapped in them. After recovery, it was used as the catalyst EC5 1 Used to catalyze new polymerization reactions; after the liquid portion is collected, it is dripped into methanol drop by drop, and light-colored or white polycarbonate gradually precipitates.
[0179] pass 1 The polycarbonate prepared in Example 23 was tested by H-NMR. The results showed that the carbonate unit content in the polycarbonate was 82% and the polymer selectivity was 55%. The TOF value of the catalytic system was calculated to be 87h -1 ; The number average molecular weight of the prepared polycarbonate measured by GPC is 15900 g / mol, and the molecular weight distribution is 1.52. The preparation reaction route is as follows Figure 6 shown.
[0180] Example 24 Preparation of polycarbonate
[0181] In a glove box, 0.015 mmol (calculated according to the aluminum content in the resin) of the recovered catalyst EC5 in Example 4 was added to the mixture. 1 and 75mmol of dry propylene oxide were added to a 5mL autoclave after dehydration and deoxygenation, and then the autoclave was taken out of the glove box, and carbon dioxide was filled into the autoclave through a carbon dioxide supply line with a pressure regulating function to make the pressure in the autoclave reach 3MPa, and the temperature of the autoclave was controlled at 70°C for polymerization reaction for 24h. After the polymerization reaction was completed, the carbon dioxide in the autoclave was slowly discharged, and the autoclave was opened and taken immediately. 1 The H-NMR sample was subjected to nuclear magnetic measurement. The unreacted propylene oxide was removed in a vacuum drying oven at 45°C to obtain a polycarbonate wrapped with a catalyst.
[0182] The polymer was fully dissolved in 10 mL of dichloromethane, and the insoluble matter was the catalyst. The solid-liquid separation was performed by extraction. The solid part was repeatedly washed with acetone until the solids were dispersed with each other and there was no obvious polymer wrapped in them. After recovery, it was used as the catalyst EC5 2 Used to catalyze new polymerization reactions; after the liquid portion is collected, it is dripped into methanol drop by drop, and light-colored or white polycarbonate gradually precipitates.
[0183] pass 1 The polycarbonate prepared in Example 24 was tested by H-NMR. The results showed that the carbonate unit content in the polycarbonate was 73% and the polymer selectivity was 79%. The TOF value of the catalytic system was calculated to be 40h -1; The number average molecular weight of the prepared polycarbonate measured by GPC is 10700 g / mol, and the molecular weight distribution is 1.27. The preparation reaction route is as follows Figure 6 shown.
[0184] Example 25 Preparation of polycarbonate
[0185] In a glove box, 0.015 mmol (calculated according to the aluminum content in the resin) of the aluminum porphyrin complex EC10 in Example 6 and 75 mmol of dried propylene oxide were added to a 5 mL autoclave after dehydration and deoxygenation, and then the autoclave was taken out of the glove box, and carbon dioxide was filled into the autoclave through a carbon dioxide supply line with a pressure regulating function to make the pressure in the autoclave reach 3 MPa, and the temperature of the autoclave was controlled at 70°C to carry out polymerization reaction for 24 hours. After the polymerization reaction was completed, the carbon dioxide in the autoclave was slowly discharged, and the autoclave was opened and taken as soon as possible. 1 The H-NMR sample was subjected to nuclear magnetic measurement. The unreacted propylene oxide was removed in a vacuum drying oven at 45°C to obtain a polycarbonate wrapped with a catalyst.
[0186] The polymer was fully dissolved in 10 mL of dichloromethane, and the insoluble matter was the catalyst. The solid-liquid separation was performed by extraction, and the solid part was repeatedly washed with acetone until the solids were dispersed with each other and no obvious polymer was wrapped in them. After recovery, it was used as the catalyst EC10 1 Used to catalyze new polymerization reactions; after the liquid portion is collected, it is dripped into methanol drop by drop, and light-colored or white polycarbonate gradually precipitates.
[0187] pass 1 The polycarbonate prepared in Example 25 was tested by H-NMR. The results showed that the carbonate unit content in the polycarbonate was 64% and the polymer selectivity was 89%. The TOF value of the catalytic system was calculated to be 87h -1 ; The number average molecular weight of the prepared polycarbonate measured by GPC is 57900 g / mol, and the molecular weight distribution is 1.38. The preparation reaction route is as follows Figure 6 shown.
[0188] As can be seen from the above embodiments, the present invention provides a supported metal porphyrin complex having a structure of formula I. The present invention is prepared by loading the metal porphyrin complex and the tertiary amine monomer on a specific functionalized carrier. Compared with the prior art, the complex has a heterogeneous property as a catalyst, and is easy to separate from the reaction system after the reaction to achieve recycling and reuse; at the same time, the catalyst simultaneously satisfies the multi-center metal synergy and the Lewis acid-base synergy between the metal porphyrin complex and the quaternary ammonium salt monomer, and the interaction can be adjusted by changing the metal center of the porphyrin monomer, the substituent of the porphyrin monomer, the loading amount of the porphyrin monomer, the type of the quaternary ammonium salt monomer and its loading amount, thereby improving the catalytic performance. The catalyst exhibits high polymer selectivity, high carbonate content, high activity and high recovery rate after separation when catalyzing the copolymerization of carbon dioxide and alkylene oxide.
[0189] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A supported metal porphyrin complex, characterized in that: It has the structure shown in formula I: The carrier is selected from a cross-linked polystyrene resin functionalized with chloromethyl; The Linker 1 is a linking group having a structure shown in Formula II-a; The N atom and connected; The Linker 2 is a linking group having a structure shown in Formula II-c: Where *′ is connected to R; The range of x and y is 0 <x<100%,0≤y<100%; The R is selected from triethylammonium chloride or trihexylammonium chloride; Said A metal porphyrin complex having a structure shown in formula III-a; In Formula III-a, R 20 Aliphatic group selected from hydrogen, halogen, C1-C10; X1 is selected from halogen; M is aluminum.
2. A supported metal porphyrin complex according to claim 1, characterized in that: The R is selected from triethylammonium chloride.
3. The method for preparing the supported metal porphyrin complex according to claim 1, characterized in that: The following steps are involved: reacting a porphyrin ligand having a structure of formula IV with an organic compound containing M and X groups to obtain a metal porphyrin complex; The metal porphyrin complex and the tertiary amine monomer react with the chloromethyl group on the cross-linked polystyrene resin to obtain a supported metal porphyrin complex having a structure of formula I; the tertiary amine monomer is triethylamine or trihexylamine; The M is aluminum; Said X is a halogen group; R1 to R19 are independently selected from hydrogen; In the structure of formula IV, * is connected to NH2.
4. Use of the supported metal porphyrin complex according to claim 1 as a catalyst in the preparation of polycarbonate.
5. The method for preparing a polycarbonate according to claim 4, characterized in that: The following steps are involved: Under the catalytic action of the above-mentioned supported metal porphyrin complex, carbon dioxide and epoxide are copolymerized to obtain polycarbonate.
6. The method for preparing a polycarbonate according to claim 5, characterized in that: The copolymerization reaction temperature is 20-150° C., the copolymerization reaction time is 8-72 hours, the carbon dioxide pressure is 2-8 MPa, and the molar ratio of the supported metal porphyrin complex to the epoxide is 1:1000-50000.
7. The method for preparing a polycarbonate according to claim 5, characterized in that: The epoxide is selected from one or more of ethylene oxide, propylene oxide, 1,2-butylene oxide, cyclohexene oxide, cyclopentane oxide, epichlorohydrin methacrylate glycidyl ether, methyl glycidyl ether, phenyl glycidyl ether and styrene alkylene oxide.